Venezuelan Migration in Peru: The Discourse of Labor Exploitation - Lovón Cueva, Marco Antonio (2021)
Migration affects both residents of the receiving country and migrants trying to improve their quality of life. One of the consequences is labor exploitation under the laws of a State or the informality of the State. Exploited workers do not usually enjoy benefits or social protections. In Peru, labor exploitation is almost common among Venezuelan immigrants who work in any job. They are poorly paid and even discriminated against. The objective of this article is to analyze the discourse of labor exploitation experienced by Venezuelan citizens in Lima-Peru. This is a qualitative study. It draws on empirical literature and narratives from a series of semi-structured interviews with Venezuelan citizens. The paper concludes that in the migrants’ discourse there are four main causes that sustain the climate of exploitation. Finally, it indicates that, in contexts of migration, all types of exploitation should be avoided and that diverse and comprehensive solutions for the migrant should be considered.